Heat transfer to Liquid Nitrogen Droplets during Cyrogenic Freezing of Foods - Hassan, Mohd Ali; Mat Hashim, Dzulkifly; Abdul Rahman, Russly (1985)
This work investigates the heat transfer phenomena that occurs when liquid nitrogen droplets fall onto a food surface. A gelatin slab was used as the food material. Liquid nitrogen was dropped on it from a dropper/reservoir system. The temperature of the slab and the droplet evaporation time were measured over a period of time. The heat transfer coefficients were calculated from these values. These are compared with the theoretical predicted values. It is seen that the experimental values are three to four times higher than the predicted values. However, if the average value of heat transfer coeff£c£ent is taken over the whole size range as the droplet evaporates, a closer agreement is obtained - the experimental values being less than twice higher.